An anthocyanin-rich extract from Zea mays L. var. ceratina alleviates neuronal cell death caused by hydrogen peroxide-induced cytotoxicity in SH-SY5Y cells - Nootchanat Mairuae; Nut Palachai; Parinya Noisa (BMC, 2024)
Abstract The incidence of dementia is rising, with neuronal cell death from oxidative stress and apoptosis recognized as a significant contributor to its development. However, effective strategies to combat this condition are lacking, necessitating further investigation. This study aimed to assess the potential of an anthocyanin-rich extract from Zea mays L. var. ceratina (AZC) in alleviating neuronal cell death. Neurotoxicity was induced in SH-SY5Y cells using hydrogen peroxide (H2O2) at a concentration of 200 µM. Cells were pretreated with varying doses (31.25 and 62.5 µg/mL) of AZC. Cell viability was assessed using the MTT assay, and molecular mechanisms including reactive oxygen species (ROS) levels, antioxidant enzyme activities (catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px)), malondialdehyde (MDA) levels for oxidative stress, and the activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2), cAMP response element-binding protein (CREB), and apoptotic factors (B-cell lymphoma 2 (Bcl-2), caspase 3) were explored. Results showed that AZC significantly improved cell viability, reduced ROS production and MDA levels, and downregulated caspase 3 expression. It enhanced CAT, SOD, and GSH-Px activities, activated ERK1/2 and CREB, and upregulated Bcl-2 expression. These findings support the neuroprotective effects of AZC, suggesting it activates ERK1/2, leading to CREB activation and subsequent upregulation of Bcl-2 expression while suppressing caspase 3. AZC may mitigate neuronal cell death by reducing ROS levels through enhanced scavenging enzyme activities. In conclusion, this study underscores the potential of AZC as a neuroprotective agent against neuronal cell death. However, further investigations including toxicity assessments, in vivo studies, and clinical trials are necessary to validate its benefits in neuroprotection.